ISO roadmap for software products - Ihrig, Aboud (Cranfield University, 2010)
The complex nature of ISO 9001 standards has been an obvious limitation for implementation. ISO 9001 accreditation provides external and internal advantages. The external benefits include increased market access and customer confidence. The internal advantages include quality improvements in both the product and process. However, this research demonstrates that the current ISO guideline for software products has not completely fulfilled the expectations in its implementation within the software organisation. Numerous companies are experiencing difficulties with ISO implementation and maintenance. Based on the analysis provided by this research, poor communication and an unsystematic approach were identified as the main current problems associated with ISO implementation. In addition, it also shows that the organisations often underestimate internal organisation factors, such as resistance to change. The existing difficulties in maintaining applied quality systems have resulted in a lack of control and monitoring. This thesis introduces an ISO Roadmap and corresponding Checklist for software products. The main goal of this ISO Roadmap is to provide enhanced transparency and assistance in the application of ISO 90003:2004 in order to make ISO implementation more manageable, visible and understandable for all people involved within the organisation. The result of this research provides the software industry with an initial step towards better systematisation and control for ISO implementations. This should help the software industry to better navigate through the ‘ISO jungle’ and facilitate an improved approach for implementation and maintenance activities. This research relied heavily on the development of the literature review, ISO 90003 standards, and knowledge from interviewees ... [cont.].
Keywords: ISO Roadmap; ISO 90003 Checklist; ISO 90003 implementation; Quality management systems; Software products